Стаціонарні та критичні точки в системах безпечної життєдіяльності - Ракітянський, Д. Б. (ХНУРЕ, 2023)
A model of two dimensional nonlinear dynamic system which reduces a detrimental factor at a reasonable price is worked out. As an empirical base model, the basis for modification, a system of ordinary nonlinear differential equations is taken. It describes the basic laws of antagonistic interaction of two factors or agents. The phase portrait shows that the system tends to a steady state in time interval, acceptable for our case. Moreover, it is possible to reduce the cost of stationary protection, or reduce the excessive level of dynamic protection impact.
Keywords: стаціонарні точки; критичні точки; системи безпечної життєдіяльності